KEHIDUPAN POLITIK DI KOTA SURAKARTA DAN YOGYAKARTA MENJELANG PEMILIHAN UMUM 1955 - Sutiyah, Sutiyah (History Department, Semarang State University and Historian Society of Indonesia, 2017)
The problem of the studied is â€œWhy Surakarta and Yogyakarta during the revolution have different attitudes and fate, but in welcoming the elections of 1955, the political partiesÂ are equally vibrant.Â This study is a historical research with utilizing sources from archives, newspapers, informant, book and previous research. The results of studied showed that the anti-colonialism/imperialism movement, nationalism, anti-feudal and democracy that became the value of the Indonesian revolution had influence to the political situation in Surakarta and Yogyakarta. The anti-feudal/anti swapraja movement in Surakarta brings consequencesÂ to the palace had lost to political power and its territory became part of administrative territory of Central Java. Political control is then held by the figure of revolution and political parties which wasnâ€™t from the elite of the palace. The oppositeÂ of true in Yogyakarta, the rulers palace became the pioneer of the revolution, so there wasnâ€™t anti-swapraja movement. Yogyakarta remained as a special region called Daerah Istimewa Yogyakarta (DIY) and the ruler of the palaceÂ existedÂ to head of DIY. The attitude of the rulers of the palace and the nobles of Yogyakarta who gave the flexibility of the establishment of the political parties toward the elections, show that they are as a consistentÂ rulerÂ to revolution value, especially erode the feudal culture and to developed democracy, even though society still has a very obedient culture (feudal trait) high against the rulers of the palace and other nobles.Â Permasalahan yang dikaji yaitu â€œmengapa Surakarta dan Yogyakarta yang pada masa revolusi memiliki sikap dan nasib yang berbeda, tetapi dalam menyambut pemilu 1955 partai-partai politik sama-sama semarakâ€. Penelitian ini merupakan penelitian sejarah dengan memanfaatkan sumber dari arsip, surat kabar, narasumber, buku dan penelitian terdahulu. Hasil penelitian menunjukkan bahwa gerakan anti kolonialisme/imperialisme, nasionalisme, antifeodal dan demokrasi yang menjadi nilai revolusi Indonesia berpengaruh terhadap situasi politik di Surakarta dan Yogyakarta. Gerakan antifeodal/antiswapraja di SurakartaÂ mengakibatkan kraton kehilangan kekuasaan politik dan wilayahnya menjadi bagian dari wilayah admnistratif Jawa Tengah. Kendali politik selanjutnya dipegang oleh tokoh revolusi dan partai politik yang bukan berasal dari kelompok elite kraton. Hal sebaliknya di Yogyakarta, penguasa kraton menjadi pelopor revolusi, sehingga tidak terjadi gerakan anti swapraja. Yogyakarta tetap sebagai daerah istimewa dengan sebutan Daerah Istimewa Yogyokarta (DIY) danÂ penguasa kraton eksis menjadi kepada DIY. Sikap peng-uasa kraton dan bangsawan Yogyakarta yang memberi keleluasaan berdirinya partai politik menyambut pemilu menunjukkan pribadi yang konsisten terhadap tuntutan revolusi, terutama untuk mengikis budaya feodal dan mengembangkan demokrasi, walaupun masyarakat masih memiliki budaya patuh (ciri feodal) yang sangat tinggi terhadapÂ penguasaÂ kraton danÂ bangsawan lainnya.Â Â